PENERAPAN TEORI BEHAVIORAL DENGAN TEKNIK MODELING UNTUK MENSTABILISASI SELF SUCCORANCE SISWA KELAS VII A4 SMP NEGERI 1 SINGARAJA - ., Ayuk Padma Wirati; ., Dra. Ni Nengah Madri Antari, M.Erg.; ., Prof. Dr. I Ketut Dharsana,M.Pd (Universitas Pendidikan Ganesha, 2015)
Penelitianinimerupakanjenispenelitiantindakan (Action Research In Counseling) yang bertujuanuntukmengetahuipenurunandanmenstabilisasiSelf SuccorancesiswakelasVII A4 SMP Negeri 1 Singarajasetelahdilaksanakanpenerapankonseling behavioral denganteknik modeling. Subjekpenelitianiniadalahsiswakelas VII A4.Penelitianiniterdiridari 4 siklusdimanamasing-masingsiklusmelaluitahapidentifikasi, diagnosa, prognosa, konseling/treatment, evaluasi/follow up, danrefleksi.Proses pengambilan data dalampenelitianinimenggunakankuesionerSelf Succorancepolaskalalinkertdandianalisissecaradeskriptifsertamenggunakanbukuharian. Berdasarkanhasilanalisis, ditemukanbahwakategoriSelf Succorancesiswapadasiklus I (BimbinganKlasikal)adalahkatagorisangatbaik 8 orang (26%), kategori baik17orang (57%), kategoricukupbaik 2 orang (6%), kategorikurangbaik 3 orang (10%), dantidakadasiswa yang memilikikategorisangatkurangbaik. JikadibandingkandengankategoriskorSelf Succorancesiswapadasiklus II(BimbinganKelompok)sebagaiberikutsiswadengankategorisangatbaik 10 orang (33%), kategoribaik 15 orang (55%), kategoricukupbaik 5 orang (17%) dantidakadasiswa yangmemilikikategorikurangbaik, dansangatkurangbaik. JikadibandingkandengankategoriskorSelf Succorancesiswapadasiklus III (KonselingKelompok) sebagaiberikut, siswa yang dengankatagorisangatbaik 15 orang (55%), kategoribaik 16 (57%), kategoricukupbaik 5 orang (25%), dantidakadasiswa yang memilikikatogorikurangbaik, kemudianjikadibandingkandengankategoriskorSelf Succorancesiswapadasiklus IV (KonselingIndividu) sebagaiberikut, siswadengankategorisangatbaik 20 orang (32%), kategoribaik 8 orang (26%) dantidakadasiswa yang memilikikategoricukupbaikdankurangbaikInimenunjukkanbahwaSelf Succorancesiswasudahstabilsecarasignifikan. Jadidapatdisimpulkanbahwakonselingbehavioral denganteknik modeling efektifdigunakanuntukmenstabilisasiSelf Succorancesiswakelas VII A4 SMP Negeri 1 SingarajaKata Kunci : behavioral, teknik modeling, Self Succorance. This study is an action research (Action Research In Counseling) which aims to determine the decline and stabilize Self Succorance A4 seventh grade students of SMP Negeri 1 Singaraja after the application of behavioral counseling use by modeling techniques. The subjects were students of class VII A4. The study consisted of four cycles in which each cycle through the stages of identification, diagnosis, prognosis, counseling / treatment, evaluation / follow-up, and reflection. The retrieval of data in this study using a questionnaire Self Succorancelinkert scale patterns and analyzed descriptively and using a diary. Based on the analysis, it was found that the category of Self Succorance students in the first cycle (Guidance Classical) is a very good category 8 people (26%), baik17 categories of people (57%), good enough category 2 (6%), unfavorable category 3 people (10%), and no students who have a very unfavorable category. When compared with the score category Self Succorance students in the second cycle (Guidance Group) as follows students with excellent category 10 people (33%), both categories of 15 people (55%), good enough category 5 people (17%) and no students who have unfavorable category, and very poorly. When compared with the score category Self Succorance students in the third cycle (Counselling) as follows, students with excellent category 15 people (55%), both categories 16 (57%), good enough category 5 people (25%), and no student who has katogori less good, then when compared to a score category Self Succorance students in cycle IV (Individual Counseling) as follows, students with excellent category 20 people (32%), both categories 8 people (26%) and not there are students who have a good enough category and unfavorable This indicates that the Self Succorance students have stabilized significantly. So it can be concluded that behavioral counseling with an effective modeling technique used to stabilize Self Succorance A4 seventh grade students of SMP Negeri 1 Singarajakeyword : behavioral counseling, modeling techniques, Self Succorance